Exploring Artaud’s Impact on Beckett’s Act Without Words II: A Study in Theatrical Influence - Cajee, Daniel Dabitlang M; Das, Nabamita (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2025)
Samuel Beckett’s Act Without Words II, a quintessential example of minimalist theatre, challenges traditional performance paradigm through its reliance on physicality and visual symbolism. This paper explores the profound impact of Antonin Artaud’s dramatic techniques on Samuel Beckett’s theatrical work, specifically within Act Without Words II. Through an analysis of stagecraft – including lighting, movement and object manipulation – this study demonstrates how Beckett was greatly influenced by Artaud. Textual analysis further substantiates the connection between Beckett’s techniques and Artaud’s theatrical vision. The findings revealed the dynamic interplay of light, physical movement, and objects in the performance, which collectively enhance audience engagement and perception. The stark contrast between light and shadow, the characters’ repetitive and ritualistic behaviours, and the strategic use of objects such as the goad and the carrot contribute to the play’s cruel resonance. By immersing the characters in states of physical and psychological struggle, Beckett cultivates a profound sense of shared suffering, compelling the audience to confront their own capacity for empathy. The analysis concludes that the synthesis of Beckett’s minimalist approach and Artaud’s emphasis on the physical and sensory, creates a truly transformative theatrical experience. Through the deliberate subversion of conventional narrative and character frameworks, both authors force the audience to engage with the elemental, unmediated aspects of human experience.